(3GdQhVJjf aj CNHGQ GdOhdJjf (B((3GdfhQjI hGdUdGMjI(B)s - (3YHO GdQMef Hf ESeGYjd Hf EHQGgje GdebOSj GdOeTbqj, CHh GdbGSe, TgGH GdOjf, CHh TGeI,J (B665 (3g` s
(3ChdgG (B:s
(3Ke ONdJ SfI CQHY hSHYjf hNeSeGFI bGd GdYeGO hcGf TeS GdOjf GdebOe ef CcGHQ GdCeQGA s
(3BNQgG (B:s
(3hJhai Gdedc GdYGOd CHhHcQ Hf CjhH HOeTb ai SfI NeS YTQI hSJeGFI QMege Gddg hhab ef Hbi ef Cgd Hjfge hCUdM PGJ Hjfge Bejf Je GdLRA GdKGfi ef GdhQVJjf hHJeGeI Je LejY GdcJGH s
(3fSNI SGHYIs
(3hYdi GdfSNI NJe eMeO CMeO GdeMQhai HJedc GdfSNIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B125s
Keywords: (3GdJGQjNs